Heredia « en gloire » - Vladimir Schotter (Babel: Littératures Plurielles, 2016)
This paper analyses the singular building of José-Maria de Heredia’s poetic ethos. His authorial image, based in its early days on a discursive ethos (which operates in Les Trophées), then conveyed by the press and the critics, and reinvested by the teachers of the first third of the 20th century has been sparking off a new horizon of expectations, which appears clearly in the pastiches and parodies of his work.